Proteome and acylome analyses of the functional interaction network between the carbazole‐degradative plasmid pCAR1 and host Pseudomonas putida KT2440. Issue 3 (16th April 2018) - Vasileva, Delyana; Suzuki‐Minakuchi, Chiho; Kosono, Saori; Yoshida, Minoru; Okada, Kazunori; Nojiri, Hideaki
Summary: Understanding the interplay between a plasmid and its host system is a bottleneck towards prediction of the fate of plasmid‐harbouring strains in the natural environments. Here, we studied the impact of the conjugative plasmid pCAR1, involved in carbazole degradation, on the proteome of Pseudomonas putida KT2440 using SILAC method. Furthermore, we investigated two acyl lysine modifications (acetylation and succinylation) that respond to the metabolic status of the cell and are implicated in regulation of various cellular processes. The total proteome analysis revealed that the abundance of key proteins involved in metabolism, signal transduction and motility was affected by pCAR1 carriage. In total, we identified 1359 unique acetylation sites on 637 proteins and 567 unique succinylation sites on 259 proteins. Changes in the acylation status of proteins involved in metabolism and translation by pCAR1 carriage were detected. Remarkably, acylation was identified on proteins involved in important plasmid functions, including partitioning and carbazole degradation, and on nucleoid‐associated proteins that play a key role in the functional interaction with the chromosome. This study provides a novel insight on the functional consequences of plasmid carriage and improves our understanding of the plasmid‐host cross‐talk.